EFEK SINERGISME AKTIVITAS ANTIBAKTERI KOMBINASI MINYAK ATSIRI BUAH ANDALIMAN (Zanthoxylum acanthopodium DC) DAN ERITROMISIN TERHADAP Streptococcus mutans DAN Streptococcus pyogenes SECARA IN VITRO - Vania Clarissha Situmorang (2023)
The concept of synergism is one of the approaches taken in dealing with the problem of antibiotic resistance. Herbal medicine such as Andaliman (Zanthoxylum acanthopodium DC) can be use as alternative antibacterial agent. Streptococcus mutans and Streptococcus pyogenes are gram-positive bacteria commonly found in the human oral cavity and these are the causative agents of various oral infectious diseases. Erythromycin is a macrolide antibiotic, commonly used in treating infections caused by gram-positive bacteria. This study aimed to determine the synergistic effect of a combination of Z. acanthopodium DC fruit essential oil and erythromycin against S. mutans and S. pyogenes. Broth microdilution method was used to determine Minimum Inhibitory Concentration (MIC) of Z. acanthpodium DC fruit essential oil and erythromycin and the checkerboard method was used to assess synergistic effect. MIC value of Z. acanthopodium DC fruit essential oil against both bacteria was 2500 ppm. Erythromycin inhibited the growth of S. mutans at MIC values 250 ppm and 1.953125 ppm against S. pyogenes. The results showed that the combination of Z. acanthopodium DC fruit essential oil and erythromycin had a synergistic effect antibacterial activity against S. mutans and S. pyogenes bacteria with a fractional inhibitory concentration index (FICI) values of 0.375 and 0.0872, respectively.